Reference Ranges for Hematological Values in Umbilical Cord Blood in Pokhara, Nepal - Basnet, Sahisnuta; Singh, Sandip Kumar; Sathian, Brijesh; Mishra, Rajnish (Journal of Nepal Paediatric Society, 2016)
Correction: Due to an error in loading the metadata, the author Sahisnuta Basnet was omitted. Sahisnuta Basnet was therefore added to the metadata on 9th January 2017. The PDF was correct. Introduction: Reference hematological values in newborns are informative in evaluation of newborns to determine state of health or disease. For a given population, reference values may differ in accordance with various factors such as age, sex, race, diet, drug intake, altitude, socio-economic status and also the method employed for determination of the values. The aim of this study was to establish reference ranges of complete blood count using umbilical cord blood of normal, healthy, full term neonates born in Manipal Teaching Hospital (MTH), Pokhara, Nepal. Material and Method: The study was conducted in 210 full term, healthy newborns delivered in MTH between Jan 2014 to Feb 2015. Cord blood was collected and a complete blood count was obtained using an automated hematology analyzer. Result: Mean hemoglobin was 15.24 ± 1.96 gm/dl and mean red blood cell count was 4.30 ± 0.63 (range 3.05 – 6.36) X 1012/L. Mean white blood cell count was 14.93 ± 4.44 (range 6.10 ± 31.7) X 109/L and platelet count was 226.88 ± 61.28 (range 105 ± 392) X 109/L. There was no significant difference found in hemoglobin, red cell, white cell and platelet counts between males and females in this study. Conclusion: The values obtained from our study provide ranges for some hematological values in healthy newborns of Pokhara Nepal. However, the hematological reference values for Nepalese cord blood needs to be confirmed by larger numbers of samples from different centers of Nepal. J Nepal Paediatr Soc 2016;36(2):160-164.